REPRESENTASI PRIA METROSEKSUAL DALAM WEB SERIES AXELERATE THE SERIES: KOSTAN AX/3 - Gunawan, Firhan; Yesicha, Chelsy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Metrosexual men get different attention in the eyes of society. Society still regards metrosexual men as gay or homosexual because they often use women's care products. But this stereotype was broken in the Axelerate The Series: Kostan AX / 3 web series. This web series highlights how men should look, be considered, and be cared for. This study discusses the representation of metrosexual women discussed in Axelerate The Series: Kostan AX / 3 Web Series.               This study uses qualitative research methods with John Fiske's semiotic analysis. Determination of informants using purposive techniques. The subject of this research is the Axelerate The Series: Kostan AX / 3 web series on the axeindonesia Youtube channel. Data obtained by the method of observation and documentation. The data analysis unit was chosen based on scenes which had 12 scenes of metrosexual men. The technique of checking the validity of the data uses triangulation of sources.        The results showed that (1) the level of reality, metrosexual men were seen in aspects of appearance, manner of speech, behavior, gestures, expressions and environment. (2) Level of representation, metrosexual men are depicted through aspects of the camera, lighting, music and sound. (3) The level of ideology, the depiction of metrosexual male values can be concluded to contain consumerism and persuasive values. Consumerism describes men who like to consume care products to support their appearance and foster self-confidence. While persuasive illustrates the web series that tries to foster a man's interest to pay more attention to his appearance by showing the expression and results of men after using care products.